Internal Audit as a Tool for Promoting Good Management in the Public Sectors in Tanzania: A Case Study of AUWSA, Arusha, Tanzania - Shishiwa, Jonathan K.; Said, Hussein R. (African Journal of Education,Science and Technology (AJEST), 2020)
The purpose of this paper was to assess the internal audit practice and process in the public sectors. In attempting to adequately discharge their responsibilities, internal auditors often find themselves in an anomalous position. This can be observed in situations and problems that are connected with the whistle-blowing, particularly when the internal job security or threatened progress of the internal auditor. The problem is the presence of massive misuses of financial resources amongst Tanzanian government agencies out of which Arusha Urban Water Supply and Sanitation Authority (AUWSA) is on the main glance. The objectives of the study included: To examine the internal audit practice and process at AUWSA. To assess the challenges encountered by the internal auditors. The Research Approach is qualitative in nature. The case study research design was used. The targeted population for this study was AUWSA staff which include Administration and other staff. Purposive/ judgmental sampling technique was used to formulate ten respondents as a sample size. The data collection methods were interview and observation. The data were analysed thematically. The findings revealed that audit practices and procedures do not comply with the International Standards on Auditing (ISA). The internal auditor faces challenges like lack of independence and technology, and negative attitude from fellow workers. The internal audit is considered as the backbone of the business accounting as it is the section that records all businesses related to the sector. The present study is unique in its examination of the relationship between internal audit factors and firm performance. The study recommends that the internal audit procedures and practices should comply with ISA. Besides, the management should ensure conducive working environment to internal auditor. Limitations in the study included: confidentiality and data storage inaccessibility of some important documents and Respondents’ Reluctance in providing Information